Indonesian Islamic Banking Transformation Strategy in the Digital Era: Analysis of Challenges, Opportunities, and Development Directions - Junda Harahap; Amhar Maulana Harahap; Putra Halomoan Hsb (Jurnal El-Thawalib, 2026)
Digital transformation has significantly changed the financial industry landscape and requires Islamic banking to adapt to remain competitive amidst developments in financial technology (fintech), neobanking, and changing customer behavior. This study aims to analyze the challenges, opportunities, and development direction of Indonesian Islamic banking in the digital era. This research is a normative legal study with a qualitative approach. The approaches used include a conceptual approach and a statutory approach. Data sources consist of primary data obtained from regulations, reports, and official publications of the Financial Services Authority (OJK), Bank Indonesia, and other relevant institutions. Secondary data are obtained from books, journal articles, previous research results, and various relevant literature. Data collection techniques were conducted through documentary studies, while data analysis was conducted qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The results show that Islamic banking in Indonesia has significant potential for growth, supported by Muslim demographics, digital economic growth, and the development of the halal industry. However, this industry still faces challenges such as low Islamic financial literacy, limited capital, and lagging technological infrastructure. Therefore, the transformation strategy needs to focus on accelerating service digitalization, strengthening capital structures, developing human resources, and optimizing real-sector financing so that Islamic banking can become a leading financial institution that is competitive, inclusive, and sustainable